Regional growth in Europe: The role of European and national policies - Llussá, Fernanda (2010)
We conduct a systematic study of the impact of European Union (EU) regional policies on regional economic growth that controls for national policies and geographic characteristics. Special care is taken in distinguishing between the impact of EU policies and of national policies on economic growth. Our empirical study tries to answer two different questions. First, is there convergence across EU regions, and if so, do regions converge to a common European steady-state or to a national one? Second, how do European and national policies affect regional growth? We find evidence of regional convergence at the national level but not at the European level. In addition we find that trade openness at the national level is associated with regional convergence while European regional policies contribute, though weakly, to regional convergence. Our results suggest that policies that foster market integration – and convergence to a common steady-state - such as the promotion of labour and capital movements across countries and common regulatory policies are as important for European-wide regional convergence as regional structural funds.